Effects of Coenzyme Q10 on Markers of Inflammation: A Systematic Review and Meta-Analysis. - Junya Zhai; Yacong Bo; Yan Lu; Chunli Liu; Lishi Zhang (PLoS ONE, 2017)
Background/objective Chronic inflammation contributes to the onset and development of metabolic diseases. Clinical evidence has suggested that coenzyme Q10 (CoQ10) has some effects on inflammatory markers. However, these results are equivocal. The aim of this systematic review was to assess the effects of CoQ10 on serum levels of inflammatory markers in people with metabolic diseases. Methods Electronic databases were searched up to February 2016 for randomized controlled trials (RCTs). The outcome parameters were related to inflammatory factors, including interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α) and C reactive protein (CRP). RevMan software was used for meta-analysis. Meta-regression analysis, Egger line regression test and Begg rank correlation test were performed by STATA software. Results Nine trials involving 428 subjects were included in this meta-analysis. The results showed that compared with control group, CoQ10 supplementation has significantly improved the serum level of CoQ10 by 1.17μg/ml [MD = 1.17, 95% CI (0.47 to 1.87) μg/ml, I2 = 94%]. Meanwhile, it has significantly decreased TNF-α by 0.45 pg/ml [MD = -0.45, 95% CI (-0.67 to -0.24) pg/ml, I2 = 0%]. No significant difference was observed between CoQ10 and placebo with regard to CRP [MD = -0.21, 95% CI (-0.60 to 0.17) mg/L, I2 = 21%] and IL-6 [MD = -0.89, 95% CI (-1.95 to 0.16) pg/ml, I2 = 84%]. Conclusions CoQ10 supplementation may partly improve the process of inflammatory state. The effects of CoQ10 on inflammation should be further investigated by conducting larger sample size and well-defined trials of long enough duration.